PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GARNITA USAHA MANDIRI KOTA TANGERANG - Sugih Pramana; Siti Aesah (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of leadership and work discipline on employee performance at PT Garnita Usaha Mandiri, Tangerang City, both partially and simultaneously. This research method uses an associative quantitative method, with a population of 82 respondents and sampling using saturated samples. Data analysis techniques use data instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, coefficient of determination tests and hypothesis tests. The results of the research show that leadership has a positive effect on employee performance with the regression equation Y = 16.220 + 0.611 (3.972 > 1.990) which means Ho1 is rejected and Ha1 is accepted. Work Discipline has a positive effect on employee performance with the regression equation Y = 12.226 + 0.703 > 1.990) which means Ho2 is rejected and Ha2 is accepted. leadership and work discipline simultaneously have a positive effect on employee performance with the regression equation Y = 9.034 + 0.334 %, and the hypothesis test obtained a value of Fcount > Ftable, namely (59.710 > 2.33) which means Ho3 is rejected and Ha3 is accepted.